Dissemination of disaster early warning messages for floods in Vosloorus Township - Ekeke, Nompumelelo Sibongile (University of the Free State, 2021)
The implementation of early warning systems by municipalities affects how communities cope with disasters such as floods. Although the technical aspects of the collection of weather and climate data have improved over the years, the dissemination of effective early warning messages to semi-urban communities remains a challenge. The main aim of this study was to investigate how the City of Ekurhuleni disseminated early warning messages to the community of Vosloorus Township during the 2019 floods from the perspective of the community. Most of the respondents stated that they did not receive early warning alerts from the municipality pertaining to these floods. Furthermore, the community’s perception is that the mechanisms used by the City of Ekurhuleni to dissemine early warning messages are not effective enough to enable community members to save lives and their properties from impending disasters. The objective of this study also included investigation of the methods and procedures used by the city to communicate early warning messages to the community of Vosloorus Township. An investigation was undertaken of disaster management policies and strategies that underpin the communication of disaster information to communities in informal settlements within Vosloorus Township. In addition, coping mechanisms implemented by the affected communities to lessen the impacts of floods were also assessed in this study. Begg, De Ramon & Lese (2021) argue that government entities must pay attention to both climatic and non-climatic information when building resilience against disaster impacts within communities. This study was conducted using mixed methods. Mixed method is defined as the implementation of two methods used to investigate a singular phenomena in a study.(Abro et al., 2015). This study used both qualitative and quantitative research methods to analyse data but also deal with the social components of early warning systems in the City of Ekurhuleni. The results of the study showed that the community of Vosloorus Township preferred the formation of community flood management committees as a measure to mitigate challenges relating to the dissemination of effective early warning messages to the community. The City of Ekurhuleni should consider implementing some improvements in the existing early warning systems to bridge the gap between the collection of weather data and ensuring that the disseminated disaster alerts reach the targeted communities.
Dissertation (M.Disaster Management (Disaster Management Training and Education Centre for Africa))--University of the Free State, 2021
Keywords: Disaster; Disaster risk management; Vulnerability; Resilience; Early warning systems; Dissemination